Induction of immunity against Hepatitis B virus surface antigen by intranasal DNA vaccination using a cationic emulsion as a mucosal gene carrier - Kim, Tae Woo; Chung, Hesson; Kwon, Ick Chan; Sung, Ha Chin; Kang, Tae Heung; Han, Hee Dong; Jeong, Seo Young (SPRINGER SINGAPORE PTE LTD, 2006)
Delivery of DNA vaccines to airway mucosa would be an ideal method for mucosal immunization. However, there have been few reports of a suitable gene delivery system. In this study we used a cationic emulsion to immunize mice via the intranasal route with pCMV-S coding for Hepatitis B virus surface antigen (HBsAg). Complexing pCMV-S with a cationic emulsion dramatically enhanced HBsAg expression in both nasal tissue and lung, and was associated with increases in the levels of HBs-specific Abs in serum and mucosal fluids, of cytotoxic T lymphocytes (CTL) in the spleen and cervical and iliac lymph nodes, and of delayed-type hypersensitivity (DTH) against HBsAg. In contrast, very weak humoral and cellular immunities were observed following immunization with naked DNA. In support of these observations, a higher proliferative response of spleenocytes was detected in the group immunized with the emulsion/pCMV-S complex than in the group immunized with naked pCMV-S. These findings may facilitate development of an emulsion-mediated gene vaccination technique for use against intracellular pathogens that invade mucosal surfaces.
Keywords: VACCINES; IMMUNIZATION; DELIVERY; SYSTEM; SARS